The occupied electronic structure of ultrathin boron doped diamond. Issue 3 (4th March 2020) - Pakpour-Tabrizi, A. C.; Schenk, A. K.; Holt, A. J. U.; Mahatha, S. K.; Arnold, F.; Bianchi, M.; Jackman, R. B.; Butler, J. E.; Vikharev, A.; Miwa, J. A.; Hofmann, P.; Cooil, S. P.; et al.
Abstract : Using angle-resolved photoelectron spectroscopy, we compare the electronic band structure of an ultrathin (1.8 nm) δ-layer of boron-doped diamond with a bulk-like boron doped diamond film (3 μm). Abstract : Using angle-resolved photoelectron spectroscopy, we compare the electronic band structure of an ultrathin (1.8 nm) δ-layer of boron-doped diamond with a bulk-like boron doped diamond film (3 μm). Surprisingly, the measurements indicate that except for a small change in the effective mass, there is no significant difference between the electronic structure of these samples, irrespective of their physical dimensionality, except for a small modification of the effective mass. While this suggests that, at the current time, it is not possible to fabricate boron-doped diamond structures with quantum properties, it also means that nanoscale boron doped diamond structures can be fabricated which retain the classical electronic properties of bulk-doped diamond, without a need to consider the influence of quantum confinement.